Errors and artifacts in coupled spectrophotometric assays of enzyme activity. - Kruger, N (1995)
This paper considers problems associated with the accurate determination of enzyme activity using coupled spectrophotometric assays. Criteria for establishing optimum assay conditions and ensuring that the coupled assay accurately reflects enzyme activity are presented. The susceptibility of such assays to interference is illustrated by five instances in which contamination of specific assay components has produced misleading estimates of phosphofructokinase and pyrophosphate:fructose 6-phosphate phosphotransferase activity. Such artifacts have resulted in publication of spurious biochemical and physiological conclusions. These examples suggest that problems associated with contaminants are likely to be widespread in coupled spectrophotometric assays, and are likely to confound interpretation of the measurements. Strategies for identifying artifacts resulting from contaminants in coupled assays are proposed.